The antitumor activity of human Vγ9Vδ2 T cells is impaired by TGF-β through significant phenotype, transcriptomic and metabolic changes - Rafia, Chirine; Loizeau, Clément; Renoult, Ophélie; Harly, Christelle; Pecqueur, Claire; Joalland, Noémie; Scotet, Emmanuel (Frontiers in Immunology, 2023)
Despite significant advances, the eradication of cancer remains a clinical challenge which justifies the urgent exploration of additional therapeutic strategies such as immunotherapies. Human peripheral Vg9Vd2 T cells represent an attractive candidate subset for designing safe, feasible and effective adoptive T cell transfer-based therapies. However, following their infiltration within tumors, gd T cells are exposed to various regulating constituents and signals from the tumor microenvironment (TME), which severely alter their antitumor functions. Here, we show that TGF-b, whose elevated production in some solid tumors is linked to a poor prognosis, interferes with the antigenic activation of human Vg9Vd2 T cells in vitro. This regulatory cytokine strongly impairs their cytolytic activity, which is accompanied by the induction of particular phenotypic, transcriptomic and metabolic changes. Collectively, these observations provide informations for better understanding and targeting the impact of TME components to regulate the antitumor activity of human T cell effectors.